Interfacing with robots: do robots do what we want them to do? - Dias, J.; Pires, N. (Futures, Microsoft’s European Innovation Magazine, 2008)
Programming an industrial robot is still an annoying task that requires too many details and expert knowledge. Each robot unit needs to be installed and prepared for a particular task, which makes the introduction of robots an expensive and risky decision